2017
DOI: 10.18632/genesandcancer.128
|View full text |Cite
|
Sign up to set email alerts
|

Active β-catenin is regulated by the PTEN/PI3 kinase pathway: a role for protein phosphatase PP2A

Abstract: Dysregulation of Wnt/β-catenin signaling has been associated with the development and progression of many cancers. The stability and subcellular localization of β-catenin, a dual functional protein that plays a role in intracellular adhesion and in regulating gene expression, is tightly regulated. However, little is known about the transcriptionally active form of β-catenin, Active Beta Catenin (ABC), that is unphosphorylated at serine 37 (Ser37) and threonine 41 (Thr41). Elucidating the mechanism by which β-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…In addition to the description of Wnt signaling above, the canonical Wnt pathway involves degradation of β-catenin by a β-TrCP1-containing E3 ligase, and alternative β-catenin degradation mediated by SIAH-1 (seven in absentia homolog-1) is responsible for the effect of CSN5 on β-catenin signaling 41 . Cross-talk occurs with other pathways including the PI3K/AKT 42 , 43 . Active β-catenin is induced by the PI3K pathway and is dependent on the phosphatase activity of the protein phosphatase PP2A 43 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the description of Wnt signaling above, the canonical Wnt pathway involves degradation of β-catenin by a β-TrCP1-containing E3 ligase, and alternative β-catenin degradation mediated by SIAH-1 (seven in absentia homolog-1) is responsible for the effect of CSN5 on β-catenin signaling 41 . Cross-talk occurs with other pathways including the PI3K/AKT 42 , 43 . Active β-catenin is induced by the PI3K pathway and is dependent on the phosphatase activity of the protein phosphatase PP2A 43 .…”
Section: Discussionmentioning
confidence: 99%
“…A decrease of E-cadherin expression is closely related to tumor development, invasion and metastasis [ 41 ], and studies have shown that E-cadherin inhibits the Wnt/β-catenin pathway through its binding at the C-terminal domain of β-catenin at the plasma membrane, thereby sequestering β-catenin from the cytoplasmic pool [ 42 ]. β-Catenin is a crucial signaling molecule in the Wnt/β-catenin signaling pathway, and dephosphorylation of β-catenin at Ser33, Ser37, and Thr41 activates β-catenin [ 43 ]. C-myc is an important member of the proto-oncogene family that regulates cell proliferation, differentiation, and programmed cell death [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from different chemical inhibitors, many natural compounds have shown to target the Wnt pathway directly or indirectly. For example Indole-3-carbinol (I3C), a natural compound present in broccoli can inhibit WWS1-mediated proteasomal degradation of PTEN, which has a direct interaction with the Wnt/beta-catenin pathway, leading to tumor regression both in vitro and in vivo (119,120). Also, there are various repressor proteins reported to downregulate β-catenin.…”
Section: Hedgehog Inhibitorsmentioning
confidence: 99%